2014
DOI: 10.1002/anie.201410720
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Engineering of a Biosensing Interface with Tetrahedral DNA Nanostructures for Ultrasensitive DNA Detection

Abstract: Self-assembled DNA nanostructures with precise sizes allow a programmable "soft lithography" approach to engineer the interface of electrochemical DNA sensors. By using millimeter-sized gold electrodes modified with several types of tetrahedral DNA nanostructures (TDNs) of different sizes, both the kinetics and thermodynamics of DNA hybridization were profoundly affected. Because each DNA probe is anchored on an individual TDN, its lateral spacing and interactions are finely tuned by the TDN size. By simply va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
266
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 375 publications
(274 citation statements)
references
References 38 publications
7
266
0
1
Order By: Relevance
“…As a universal biosensing platform, we have tested this protocol to detect DNA, microRNA (mir-21, mir-141 and others), proteins (antigens such as prostate-specific antigen (PSA), thrombin and others) and small molecules (cocaine) [19][20][21][22][23][24][25][26] . Furthermore, we have used our detection platform to detect target molecules in complicated biological fluids such as cell lysates, tissue extracts and human serum, and we observed excellent sensing performance.…”
Section: Applications Of the Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a universal biosensing platform, we have tested this protocol to detect DNA, microRNA (mir-21, mir-141 and others), proteins (antigens such as prostate-specific antigen (PSA), thrombin and others) and small molecules (cocaine) [19][20][21][22][23][24][25][26] . Furthermore, we have used our detection platform to detect target molecules in complicated biological fluids such as cell lysates, tissue extracts and human serum, and we observed excellent sensing performance.…”
Section: Applications Of the Methodsmentioning
confidence: 99%
“…Next, we thoroughly investigated the programmability of the DNA-nanostructure-based biosensing interface. We demonstrated that the use of TDNs with various precise sizes supported a 'soft lithography'-like means to engineer the interface for electrochemical DNA sensing 20 . Then, we generalized our with the aid of structural prediction tools (e.g., RNAstructure and NUPACK software) to predict the secondary structure 20 .…”
Section: Development Of the Protocolmentioning
confidence: 99%
See 3 more Smart Citations